Exercise Similarly Facilitates Men and Women’s Selective Attention Task Response Times but Differentially Affects Memory Task Performance - Coleman, Matt; Offen, Kelsey; Markant, Julie (Frontiers in Psychology, 2018)
Previous research has found that acute, moderate-intensity physical exercise enhances selective attention and memory and that men and women show differential performance on tasks measuring these skills. Although exercise and participant sex have been examined separately, it remains unknown whether acute, moderate-intensity exercise differentially affects men and women’s selective attention and memory encoding and retrieval. To address this question, participants in the present study completed two 10-minute sessions of moderate-intensity exercise comprised of jumping rope alternating with walking in place. Each participant completed a selective attention task and a task assessing recognition and object location memory immediately after exercising. Exercise was related to overall faster performance during the selective attention task, with no differences in men and women’s performance. Women showed better recognition memory compared to men. Exercise specifically improved object location memory among men, but only among participants who completed the memory task second. These findings suggest that acute, moderate-intensity exercise differentially affects men and women’s memory, which may be related to complex interactions between exercise, sex hormones, and the neurotrophin BDNF.